Troglitazone and Δ2Troglitazone Enhance Adiponectin Expression in Monocytes/Macrophages through the AMP-Activated Protein Kinase Pathway - Tsai, Jaw-Shiun; Chuang, Lee-Ming; Chen, Ching-Shih; Liang, Chan-Jung; Chen, Yuh-Lien; Chen, Ching-Yu (Mediators of Inflammation, 2014)
Accumulating evidence indicates that the regimen to increase adiponectin will provide a novel therapeutic strategy for inflammation and cardiovascular disorders. Here, we tested the effect of troglitazone (TG) and its newly synthesized derivative, 5-[4-(6-hydroxy-2,5,7,8-tetramethyl-chroman-2-yl-methoxy)-benzylidene]-2,4-thiazolidinedione (Δ2troglitazone, (Δ2TG)), on the adiponectin expression in monocytes/macrophages and the relative mechanisms. The expression of adiponectin was located in macrophages of atherosclerotic lesions from patients and cholesterol-fed rabbits. TG and Δ2TG enhanced adiponectin mRNA and protein expression in THP-1 cells by quantitative real-time PCR, Western blot, and immunocytochemistry. TG induced adiponectin mRNA expression through a PPARγ-dependent pathway whereas Δ2TG enhanced adiponectin mRNA expression through a PPARγ-independent pathway in THP-1 cells. Both TG and Δ2TG enhanced adiponectin mRNA expression through AMP-activated protein kinase (AMPK) activation. TG and Δ2TG decreased the adhesion of THP-1 cells to TNF-α-treated HUVECs and the inhibitory effect was abolished by specific antiadiponectin antibodies. TG- and Δ2TG-induced suppression on monocyte adhesion were inhibited by a selective AMPK inhibitor compound C. Our data suggest that the inhibitory effect of TG and Δ2TG on monocyte adhesion might be at least in part through de novo adiponectin expression and activation of an AMPK-dependent pathway, which might play an important role in anti-inflammation and antiatherosclerosis.